Improving health system readiness to address violence against women and girls: a conceptual framework - Manuela Colombini; Susannah H. Mayhew; Claudia García-Moreno; Ana Flavia d'Oliveira; Gene Feder; Loraine J. Bacchus (BMC, 2022)
Abstract Background There is an increasing focus on readiness of health systems to respond to survivors of violence against women (VAW), a global human rights violation damaging women's health. Health system readiness focuses on how prepared healthcare systems and institutions, including providers and potential users, are to adopt changes brought about by the integration of VAW care into services. In VAW research, such assessment is often limited to individual provider readiness or facility-level factors that need to be strengthened, with less attention to health system dimensions. The paper presents a framework for health system readiness assessment to improve quality of care for intimate partner violence (IPV), which was tested in Brazil and Palestinian territories (oPT). Methods Data synthesis of primary data from 43 qualitative interviews with healthcare providers and health managers in Brazil and oPT to explore readiness in health systems. Results The application of the framework showed that it had significant added value in capturing system capabilities - beyond the availability of material and technical capacity - to encompass stakeholder values, confidence, motivation and connection with clients and communities. Our analysis highlighted two missing elements within the initial framework: client and community engagement and gender equality issues. Subsequently, the framework was finalised and organised around three levels of analysis: macro, meso and micro. The micro level highlighted the need to also consider how the system can sustainably involve and interact with clients (women) and communities to ensure and promote readiness for integrating (and participating in) change. Addressing cultural and gender norms around IPV and enhancing support and commitment from health managers was also shown to be necessary for a health system environment that enables the integration of IPV care. Conclusion The proposed framework helps identify a) system capabilities and pre-conditions for system readiness; b) system changes required for delivering quality care for IPV; and c) connections between and across system levels and capabilities.